2020
DOI: 10.1016/j.stem.2020.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of Lgr5-Negative Cancer Cells Drives Metastasis in Colorectal Cancer

Abstract: Highlights d The majority of disseminating cells of colorectal cancer are Lgr5 À d Lgr5 À cancer cells are the main seeds of colorectal cancer metastatic lesions d Long-term metastatic growth from Lgr5 À cells requires appearance of Lgr5 + cells d Lgr5 À metastases have the intrinsic capacity to re-establish the cellular hierarchy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
196
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(226 citation statements)
references
References 56 publications
(76 reference statements)
6
196
1
1
Order By: Relevance
“…Stem cells, often defined as a pool of cells sustained at the apex of cell hierarchies or developmental trajectories, are traditionally seen as unique drivers of tissue homeostasis and regeneration of normal tissue, but also of metastasis and therapy-resistance in cancer 52 . However, recent studies have shown metastasis and stemness can be uncoupled in colorectal cancer metastasis 53 , and that oncogenic mutations and paracrine signals can reverse developmental trajectories so that more differentiated cells can regain stem cell characteristics [54][55][56] . Here, we show that a gradient of ERK target gene expression is associated with developmental latent time in CRC organoids, extending our previous finding of graded ERK activity in CRC organoids 57 .…”
Section: Mapk Target Gene Expression Defines Crc Differentiation Statesmentioning
confidence: 99%
“…Stem cells, often defined as a pool of cells sustained at the apex of cell hierarchies or developmental trajectories, are traditionally seen as unique drivers of tissue homeostasis and regeneration of normal tissue, but also of metastasis and therapy-resistance in cancer 52 . However, recent studies have shown metastasis and stemness can be uncoupled in colorectal cancer metastasis 53 , and that oncogenic mutations and paracrine signals can reverse developmental trajectories so that more differentiated cells can regain stem cell characteristics [54][55][56] . Here, we show that a gradient of ERK target gene expression is associated with developmental latent time in CRC organoids, extending our previous finding of graded ERK activity in CRC organoids 57 .…”
Section: Mapk Target Gene Expression Defines Crc Differentiation Statesmentioning
confidence: 99%
“…Moreover, a recent study reported that acute promyelocytic leukemia cells undergoing differentiation driven by retinoic acid could re-acquire the LIC state following chemotherapy withdrawal, effectively reversing the differentiation trajectory (McKenzie et al, 2019). Extending this concept to solid tumors, a similar effect was recently uncovered in colon cancer, where cells devoid of the stem cell marker Lgr5 can establish metastases and give rise to Lgr5 + cancer stem cells (Fumagalli et al, 2020). These findings parallel the known phenomenon that in healthy tissues, adult stem cell identity can be plastic: professional stem cells maintain tissue integrity at steady state, but under stress, facultative stem cells can be recruited from apparently lineage-committed populations (Raven et al, 2017;Tata et al, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…Certainly, Fumagalli and colleagues observed most disseminated CRC cells in circulation to be LGR5 negative. Latter cells formed distant metastases in which CSC appeared LGR5 positive [ 54 ]. This plasticity of CCSC may explain the relatively low level of LGR5 , as BKZ-2 and BKZ-3 also revealed an EMT-phenotype reflected by a high level of SLUG.…”
Section: Discussionmentioning
confidence: 99%